2016
DOI: 10.1021/acs.energyfuels.6b02084
|View full text |Cite
|
Sign up to set email alerts
|

Some Compositional Viscosity Correlations for Crude Oils from Russia and Norway

Abstract: The current work is based on experimental viscosity and compositional data of about 200 crude oil samples from various part of Russia and Norwegian continental shelf. Data analyses were performed to estimate correlations between viscosity and density values, as well as concentrations of main components from the crude oils of different origin. It appeared that in some cases it is possible to establish a general correlation of viscosity increase along with growing asphaltene, resin, and aromatics contents, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…30 Applications of many sophisticated methods for the evaluation of asphaltenes (such as time-resolved fluorescence depolarization, laser ionization mass spectrometry, AFM, and STM) have reduced the chemical uncertainties substantially, 17 but contradictory conclusions may be presented for understanding the relationship between the compositions and apparent properties of heavy crude oil. Researchers have established a general correlation of viscosity increase along with increasing asphaltene, resin, and aromatics concentrations and a decrease in viscosity with increasing saturate concentration, 31 but another article mentioned that resins "mitigated" the influence of asphaltenes, facilitating the disaggregation and stabilizing of the system as a whole. 32 Keep in mind, the concept of asphaltenes and resins are not definite, which depends on the method of determining their concentration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30 Applications of many sophisticated methods for the evaluation of asphaltenes (such as time-resolved fluorescence depolarization, laser ionization mass spectrometry, AFM, and STM) have reduced the chemical uncertainties substantially, 17 but contradictory conclusions may be presented for understanding the relationship between the compositions and apparent properties of heavy crude oil. Researchers have established a general correlation of viscosity increase along with increasing asphaltene, resin, and aromatics concentrations and a decrease in viscosity with increasing saturate concentration, 31 but another article mentioned that resins "mitigated" the influence of asphaltenes, facilitating the disaggregation and stabilizing of the system as a whole. 32 Keep in mind, the concept of asphaltenes and resins are not definite, which depends on the method of determining their concentration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A simple way to reduce heavy crude oil transportation costs is removing of heavy components from it, namely asphaltenes, [ 41 ] which contribute significantly to the high viscosity of these oils. [ 42,43 ] Thereby, there is the problem of rationally utilization of asphaltenes generated after oil deasphalting. It seems that the best way to solve this environmental problem is to give the asphaltenes an added value.…”
Section: Introductionmentioning
confidence: 99%
“…6, between the power constant and the ratio Resins (wt%)−0.4×Asphaltenes (wt%) ν , a correlation coefficient of 0.99 was obtained, indicating proportionality between the K r K a and the ratio. Malkin et al showed that the small concentrations of asphaltenes have a dominant influence on the viscosity, while much higher concentrations of resins and aromatics are required in order to cause a significant increase of oil viscosity [32]. Resins contribute to dispersion of asphaltene nanoaggregates, increase the solubility of asphaltenes in oil and decrease the effect of asphaltenes on viscosity through reducing the size of asphaltene aggregates [33][34][35].…”
Section: Resultsmentioning
confidence: 99%